Diseño arquitectónico de un centro cultural para el recinto Las Maravillas en la provincia de Manabí - Pérez Izurieta, Abigail Alexandra (2023)
Culture plays a fundamental role in the economic development of societies, and cultural institutions, are not considering places for the preservation and dissemination of artistic expressions, but also tools for progress, social integration, and economic development. The province of Manabí, in Ecuador, has a rich cultural history and remarkable social development. The Cascol parish has a rich cultural heritage and traditions rooted in its population, which is preserved and promoted through festivals, events and cultural activities that allow the community to share and celebrate its cultural identity. The investigation will be divided into four chapters, representing each stage of the inquiry process to arrive at a formal proposal. The investigation analyzes the problem in the "Las Maravillas" complex in terms of its cultural, social, and economic development, establishing general and specific objectives, justification, scope, and assumptions, guiding the investigation, and obtaining information.